1991
DOI: 10.1111/j.1524-4725.1991.tb03642.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryotherapy in the Treatment of Condylomata Acuminata: A Controlled Study of 64 Patients

Abstract: A clinical controlled study is presented for the treatment of condylomata acuminata with cryotherapy in 64 patients. Condylomata resolved in 83% within 4 weeks and 96% after 6 weeks by using cryotherapy. The results were significantly better compared with the control group of 70 patients (13% and 45% after 4 weeks and 6 weeks, respectively). Other therapeutic modalities are reviewed. Cryotherapy is an elegant and effective method for the treatment of condylomata acuminata without discomfort to the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 3 publications
1
13
0
3
Order By: Relevance
“…Anogenital wart recurrence rates in immunocompetent individuals after trichloroacetic acid, podophyllin, podophyllotoxin, cryotherapy and electrodessication have been reported to be of 36%, 40%, 25%, 32% and 25%, respectively (Godley et al, 1987;Bashi, 1985;Edwards and Atma-Ram, 1988;Mazurkiewicz and Jablonska, 1986;Abdullah et al, 1993;Beutner et al, 1989;Beutner and Ferenczy, 1997;Greenberg et al, 1991;Stone et al, 1990;Damstra and Van Vloten, 1991). In our study we have observed a wart recurrence rate of 11.76% at 3 months and of 29.4% in the 6-month follow up.…”
Section: Discussionsupporting
confidence: 51%
“…Anogenital wart recurrence rates in immunocompetent individuals after trichloroacetic acid, podophyllin, podophyllotoxin, cryotherapy and electrodessication have been reported to be of 36%, 40%, 25%, 32% and 25%, respectively (Godley et al, 1987;Bashi, 1985;Edwards and Atma-Ram, 1988;Mazurkiewicz and Jablonska, 1986;Abdullah et al, 1993;Beutner et al, 1989;Beutner and Ferenczy, 1997;Greenberg et al, 1991;Stone et al, 1990;Damstra and Van Vloten, 1991). In our study we have observed a wart recurrence rate of 11.76% at 3 months and of 29.4% in the 6-month follow up.…”
Section: Discussionsupporting
confidence: 51%
“…Burning and itching sensations are accompanied by the application of TCA. Infection, ulceration and scarring are the rare side‐effects of TCA …”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] Cryotherapy involves application of nitrous oxide or liquid nitrogen to the warts, inducing dermal and vascular damage and leading to both epidermal and dermal cellular necrosis. Cryotherapy is effective; however, there is always a fear of scarring caused by the wound created.…”
Section: Discussionmentioning
confidence: 99%